Kepastian Hukum Larangan Notaris Merangkap Jabatan sebagai Pimpinan Badan Usaha (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
The provision under Article 17 paragraph (1) letter f of the Notary Law (UUJN) stipulates that a Notary is prohibited from concurrently holding a position as a leader or manager in a state-owned or private business entity. However, the term "leader" as used in this provision is not clearly defined, either in the main text of the article or in its explanatory section. The absence of a clear definition creates legal ambiguity, as the provision does not refer to organizational structures regulated under the Company Law, the State-Owned Enterprises Law, or the Regional Government Law. This has led to varying interpretations in the supervision of Notaries and creates potential inconsistencies in the enforcement of the rule. To address this normative uncertainty, there is a need for regulation that explicitly outlines which positions are considered to fall under the term "leader" as intended by the UUJN. This journal article focuses on analyzing the meaning of the term "leader" in Article 17 paragraph (1) letter f of the UUJN, and on examining the legal certainty of using the term in relation to the prohibition against Notaries concurrently holding leadership positions in business entities.